The Contemporary Engish - Indonesian Dictionary With British and American Pronunciation and spelling : Volume Two (M - Z) - Salim, Peter (Jakarta:Media Eka Pustaka, 2006)
Koleksi Referensi (Tidak Dipinjamkan)